Polymyxins: recent advances and challenges - Yang, Shan; Wang, Hairui; Zhao, Dan; Zhang, Shurong; Hu, Chenggong (Frontiers in Pharmacology, 2024)
Antibiotic resistance is a pressing global health challenge, and polymyxins have emerged as the last line of defense against multidrug-resistant gram-negative (MDR-GRN) bacterial infections. Despite the longstanding utility of colistin, the complexities surrounding polymyxins in terms of resistance mechanisms and pharmacological properties warrant critical attention. This review consolidates current literature, focusing on polymyxins antibacterial mechanisms, resistance pathways, and innovative strategies to mitigate resistance. We are also investigating the pharmacokinetics of polymyxins to elucidate factors that influence their in vivo behavior. A comprehensive understanding of these aspects is pivotal for developing next-generation antimicrobials and optimizing therapeutic regimens. We underscore the urgent need for advancing research on polymyxins to ensure their continued efficacy against formidable bacterial challenges.